Microeconomics - Hubbard, R. Glenn; e utor9 (Pearson, 2006)
Markets in Action.- Firms in the Domestic and International Economies.- Microeconomic Foundations: Consumers and Firms.- Market Structure and Firm Strategy.- Markets for Factors of Production.- Information, Taxes, and the Distribution of Income
Keywords: Microeconomía